Best Hotel Selection Decision Support System using MOORA Method - Zai, Iwanman; Barkat Harefa; Mesran; Hetty Rohayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of hotels has become an important part of the tourism industry, with the main function as a place to stay for guests. Hotels have evolved from simple structures to complex ones that offer various facilities and services to meet various guest needs. This study focuses on developing a system that can assist in making hotel selection decisions by considering various criteria such as hotel area, price, and room type. The problem discussed in this study is the difficulty in choosing the best hotel among many choices, which can be influenced by various factors. The purpose of this study is to design a system that can effectively evaluate and rank hotels based on their attributes, so that the decision-making process becomes more efficient and accurate. The MOORA method is used in this study to evaluate hotels based on their attributes. This method is very useful in situations where there are several criteria that are not mutually exclusive, allowing for a more comprehensive evaluation. This study uses a combination of data collection, definition of alternative criteria, and weighting to create a decision matrix. The results of this study demonstrate the effectiveness of the MOORA method in selecting the best hotel based on predetermined criteria. The result of this study is a decision support system that can be applied in various contexts where hotel selection is a crucial decision. This system provides a structured approach to evaluating hotels, ensuring that selection is based on a thorough analysis of the available options. This research contributes to the development of more effective decision-making tools in the hospitality industry, ultimately improving the overall customer experience.